2022
DOI: 10.4018/978-1-7998-9664-7.ch015
|View full text |Cite
|
Sign up to set email alerts
|

Rural Tourism and Its Impact on the Economy

Abstract: The changing tastes and preferences of tourists have given rise to a new form of tourism, rural tourism. This new form of tourism plays an important role to change the rural economy and living standard of villagers. Meghalaya, the abode of clouds, is famous for a number of its villages and attract thousands of tourists every year. This research aims to study the impact of rural tourism on the economy of the village. For this study, Ialong village has been selected, and 150 people were interviewed with the help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Control variables . Scholars have observed that the level of digital village development is influenced by various factors, including capacity for economic development, rural population size, and population age structure [ 75 , 76 ]. Therefore, these three variables are chosen as control variables.…”
Section: Methodsmentioning
confidence: 99%
“…Control variables . Scholars have observed that the level of digital village development is influenced by various factors, including capacity for economic development, rural population size, and population age structure [ 75 , 76 ]. Therefore, these three variables are chosen as control variables.…”
Section: Methodsmentioning
confidence: 99%